2015
DOI: 10.1007/s00441-015-2179-7
|View full text |Cite
|
Sign up to set email alerts
|

Expression of ectonucleotidases in the prosencephalon of melatonin-proficient C3H and melatonin-deficient C57Bl mice: spatial distribution and time-dependent changes

Abstract: Extracellular purines (ATP, ADP, AMP and adenosine) are important signaling molecules in the CNS. Levels of extracellular purines are regulated by enzymes located at the cell surface referred to as ectonucleotidases. Time-dependent changes in their expression could profoundly influence the availability of extracellular purines and thereby purinergic signaling. Using radioactive in situ hybridization, we analyzed the mRNA distribution of the enzymes NTPDase1, -2 and -3 and ecto-5'-nucleotidase in the prosenceph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 48 publications
0
10
0
3
Order By: Relevance
“…In the C3H group, there was higher activity on short, warm nights, while the C57Bl group did not show any trend at all. Notably, the C3H mice were more active under the outdoor conditions as compared with the C57Bl animals, whereas, under laboratory conditions, the total activity levels of the 2 strains did not differ (Homola et al, 2015; Wicht et al, 2014).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In the C3H group, there was higher activity on short, warm nights, while the C57Bl group did not show any trend at all. Notably, the C3H mice were more active under the outdoor conditions as compared with the C57Bl animals, whereas, under laboratory conditions, the total activity levels of the 2 strains did not differ (Homola et al, 2015; Wicht et al, 2014).…”
Section: Discussionmentioning
confidence: 91%
“…Much of our knowledge of the circadian system and its entrainment (i.e., the responses to abiotic cues such as light or temperature, as well as masking effects, entrainment, chronotype, and rhythm stability) have been studied almost exclusively in the laboratory under standardized conditions (Homola et al, 2015; Mrosovsky, 1996; Pfeffer et al, 2012; Refinetti, 2002; Refinetti, 2004; von Gall et al, 1998; Wicht et al, 2014).…”
mentioning
confidence: 99%
“…Actograms and activity profiles were created using Clocklab software (Actimetrics, Wilmette, Ill., USA) as described [34,35] . The daytime activity was expressed in percent of the total/daily (24 h) activity as described [34,36] .…”
Section: Recording Of Food Intake and Locomotor Activitymentioning
confidence: 99%
“…Recently, Homola and co-workers [21] suggested that melatonin regulates the expression of brain ectonucleotidases; therefore, the anti-inflammatory role of melatonin may involve the regulation of signaling via P2 receptors, including endothelial P2Y 1 R. However, no studies have addressed the effect of melatonin on purinergic P2Y receptor signaling. Here, we show that melatonin in the nM range of concentration inhibited the P2Y 1 R-induced leukocyte adhesion to rat endothelial cells and TNF-α production in vitro, suggesting melatonin as a novel modulator of purinergic signaling.…”
Section: Introductionmentioning
confidence: 99%